From birth to adulthood: An analysis of the Brazilian lancehead (Bothrops moojeni) venom at different life stages - Hatakeyama, Daniela Miki (PLoS One, 2021)
The Brazilian lancehead (Bothrops moojeni) has a wide distribution in Brazil and represents a serious public health hazard. Previous works reported that the symptoms of snakebites caused by B. moojeni juveniles’ bites were mainly related to coagulation, while those caused by adults’ bites had a more prominent local damage. In this work, we analyzed the venoms of B. moojeni at different life stages to better understand the ontogeny shift in this species. Snakes were grouped by age and sex, and venom pools were formed accordingly. Compositional analyses by one-dimensional electrophoresis (1-DE), chromatography, and mass spectrometry revealed that ontogenetic changes might be mostly related to phospholipase A(2) (PLA(2)) and metalloproteases. Regarding the venoms functional aspect, proteolytic, L-amino acid oxidase, PLA(2), and coagulant in vitro activities were assayed, but only the first and the last ones showed age-related changes, with the venom of snakes up to 1 year-old displaying lower proteolytic and higher coagulant activities, while those from 2 years-old onward presented the opposite relation. The venoms of 3 years-old snakes were exceptions to the compositional and functional pattern of adults as both venoms presented profiles similar to neonates. Sex-related differences were observed in specific groups and were not age-related. In vivo experiments (median lethal dose and hemorrhagic activity) were statistically similar between neonates and adults, however we verified that the adult venom killed mice faster comparing to the neonates. All venoms were mostly recognized by the antibothropic serum and displayed similar profiles to 1-DE in western blotting. In conclusion, the Brazilian lancehead venom showed ontogenetic shift in its composition and activities. Furthermore, this change occurred in snakes from 1 to 2 years-old, and interestingly the venom pools from 3 years-old snakes had particular characteristics, which highlights the importance of comprehensive studies to better understand venom variability.